KOMPARASI PENAMBANG MINYAK TRADISIONAL BOJONEGORO DAN PENAMBANG TIMAH TRADISIONAL BANGKA BELITUNG: COMPARATION OF BOJONEGORO TRADITIONAL OIL MINERS AND TRADITIONAL TIN MINERS OF BANGKA BELITUNG - April, Aprilia Natasya; Aprillia , Donna Ardila; Maulana, Muhamad; Ruslan, Ruslan (eScience Humanity Journal, 2024)
This research relates to Natural Resources of oil and gas in Indonesia, which are important commodities in the Indonesian and regional economies, as well as the impact on oil producing areas, especially Wonocolo Village and Bangka Belitung. The aim of this research is to compare the portrait of traditional oil mining in Wonocolo Village and in Bangka Belitung from an economic, social, political and environmental perspective. The type of research method used is descriptive qualitative field research. The data collection technique was carried out through gradual interviews to find out and analyze the differences that exist in the two selected regions. From this research it was found that from an economic perspective, oil mining is an important sector in income and economic growth in the two regions, however the welfare of workers and communities around oil mining is still very unequal from the results obtained from oil mining. The Wonocolo Village community is fully given the authority to manage existing traditional oil mining, while traditional oil mining in Bangka Belitung is more controlled by foreign companies and the state so the political aspect is very strong.Meanwhile, from a social perspective, traditional oil mining has had a positive impact on the Human Development Index (HDI) in the two regions and has had a real impact with the growth of HDI, the economy and regional development continuing to develop every year. The existence of traditional oil mining has a real impact on damage to the surrounding environment, ranging from pollution to ecosystem damage. From the findings above, it can beconcluded that oil mining has many positive and negative impacts on economic, social, political and environmental aspects in local communities.